Work‐to‐Family Spillover Effects of Workplace Ostracism: The Role of Work‐Home Segmentation Preferences. Issue 1 (24th January 2013) - Liu, Jun; Kwan, Ho Kwong; Lee, Cynthia; Hui, Chun
Abstract This study considers workplace ostracism as a source of stress and examines its spillover effects on the family. By integrating the work‐family interface model with boundary theory, we investigate the impact of workplace ostracism as perceived by employees on their family satisfaction by examining the mediating role of work‐to‐family conflict and the moderating role of work‐home segmentation preferences. The results from a three‐wave field survey of 233 employees in China indicate that workplace ostracism is negatively related to family satisfaction; this relationship is also mediated by work‐to‐family conflict. In addition, work‐home segmentation preferences attenuate the mediating effect of work‐to‐family conflict on the relationship between workplace ostracism and family satisfaction. The theoretical and managerial implications of these findings are discussed.